An ontology proposal for a corpus of letters of Vincenzo Bellini: formal properties of physical structure and the case of rotated texts. (28th September 2022) - Cristofaro, Salvatore; Sichera, Pietro; Spampinato, Daria
In this paper the formal OntoBelliniLetters ontology is described concerning the corpus of Vincenzo Bellini's letters kept at the Belliniano Civic Museum of Catania. This ontology is part of a wider project - the BellinInRete project - one of whose aims is the development of a more general and complete ontology for the whole of Vincenzo Bellini's legacy preserved in the museum. The main concepts and relations building up the ontology knowledge base are described and discussed and some formal properties of them are presented. The ontology schema is inspired by the CIDOC Conceptual Reference Model (CIDOC CRM).